EKOLOGI KONSTITUSI: Antara Rekonstruksi, Investasi Atau Eksploitasi Atas Nama NKRI - Mukhlish Mukhlish; Mustafa Lutfi (The Constitutional Court of the Republic of Indonesia, 2016)
This state is basically recognized as a rich state, either in term of ecological side or in term of cultural potency and ideological varieties, as the inheritance of motherland. However, this is so sad when we ironically saw a bunch of tragedies which are tragically occurred, start from tsunami, and other issues such as the scandal of century that seems to be unsolved! Moreover, nowadays, the environmental problem has occurred and reached its highest culmination point. The environmental destruction and pollution process have uncontrollably happened. Noting so many catastrophes happened anywhere in this state; such as floods, landslides, earthquakes, lapindo mud tragedy, roads vanishing, illegal logging, forest function shift, and many others, is so an ironic thing. These all catastrophes become such a sign of inharmonic relationship exist between the state, human and the environment. Then, should we always blame these disaster s for the governments’ fault that, in such this multidimensional crises and demoralization that full of utopia and ironical images, seems to be unaware of their main position? The law is neutered and naked from its constitutional essence. This terrible condition can be impossibly happened when our representatives in the government are loyally take taken a side of the important of their party through the political campaign appointments which seem to face stagnation in its implementation and not loyal to the true mandator. Perceiving this such phenomenon, we need not only a kind of law penetratin that progressifely and integratifally can become an elegant problem solving for achieving of the aims of ongoing developmnet that can fully protect the importance of the environment and human life intentions but a moral forces and people power that should be continuallly implemented. Hence, the urgency of law management, ecological tutorial awaraness and the success of environmetal living management in term of national law development, becomes a final destination of this writting. Moreover , this writing is a kcorrection of the unclear control and maintenanceof the law of environmental administration.